What factors are most important in a state’s decision to abide to or refrain from international security regimes? Exploring the strategic motivations behind Libya’s decision to abandon its nuclear weapons program and Israel’s refusal to do so - Barre, Annelise Helene Kevin (2021)
What Causes Nuclear Proliferation or Nuclear Rollback? Answering this question will help us understand the factors behind state decisions to join international regimes of security. Understanding why states abide or retrain from international security regimes will help us to address current obstacles to non-proliferation in the Middle East; Why, after many years of trying, are we unable to put in place a Nuclear Weapons Free Zone in the Middle East? What is in store for the 2015 Iran Nuclear Deal now that a new democrat administration has come to office in the United States? These findings will be particularly pertinent in forecasting if the growing security tensions between Iran, and by extension Hezbollah, and its regional “enemies” push it to pursue nuclear weapons development. Or, on the contrary if the country´s rapidly degrading economy push it back to the negotiating table1 . With a new American administration in place, the democrats will have to make a decision on which outcome is most likely. The three dominant factors explaining nuclear behavior are first, the presence of threats to security; second, the extent of a state’s economic and political integration into the global system; and lastly the existence of security guarantees to a state. In this paper I will assess the validity of the three dominant arguments for explaining nuclear behavior of states by conducting a case comparison between Israel’s decision not to join the Nuclear NonProliferation Treaty, and Libya’s decision to undergo and subsequently abandon Nuclear Weapons development. I will show how the continuous and significant threats to Israeli security diminishes the impact that the two other factors have, and further how the lack of significant threats to Libyan security caused its economic and political isolation from the international community to play the decisive role in its nuclear rollback. Furthermore, these case studies will highlight how security guarantees are only decisive in light of a protected state’s perception of their legitimacy. These findings will help shed some light on which non-proliferation policies should be adopted if we ever wish to see a Nuclear Weapons Free Zone in the Middle East.